An Expert System for Wood Anatomy Research, Image Display and Wood Identification - Gupta, Sangeeta; Kulshreshta, S. P.; Chauhan, Laxmi (Indian Forester, 2002)
An expert system entitled ’Wood Anatomy Information System (WAIS)’ has been developed for assisting in wood research, wood images display and wood identification. The software is quite comprehensive with provision for all details related to FRI Xylarium and anatomical structure of Indian hardwoods. It is user friendly and has five modules viz. feature description; data input and image display; wood identification; query; and report generation. The database on wood microstructure is developed using standard list of anatomical characters given by International Association of Wood Anatomists (IAWA). The same is used in deciphering information of interest and comparing different data sets of various families, genera and species. The data thus generated shall help in establishing phylogenetic relationship, microstructure variation, homogeneity and heterogeneity within families, relationship between features and above all in wood identification. Since the woods are studied on three planes therefore Wood Images of all the three surfaces viz transverse, radial and tangential shall be stored in this package. The same will serve the purpose of wood structure atlas. The system carries out identification through binary search. The computer filters as per the selected features and gives option of best subsequent feature that can narrow down the search considerable. Thus in about four to five steps the identification of an unknown wood sample can be achieved. This identification module has the flexibility of skipping the features not known to the user. Through Querying module selected taxa can be related to selected features so as to reflect upon the structural affinity between various features, species, genus and families. The Report module generates identification key for the family, genera or species.